PENGARUH KOMPETENSI, KETERLIBATAN KERJA GURU DAN KOMPENSASI TERHADAP KINERJA GURU SEKOLAH MENENGAH KEJURUAN NEGERI BATAM KEPULAUAN RIAU - deni asmarazisa (BENING, 2019)
ABSTRACT         Effect of Competence, Work Involvement and Employment Compensation on teachers on teacher performance at Batam State Vocational High School. This study aims to determine the effect of teacher work competency and work involvement and compensation for the performance of Batam State Secondary School Teachers. Sources of data found are primary data obtained directly from the answers from the questionnaire concerned with the research with the above qualifications. Coupled with several references from the researchers themselves. Based on this study, the Competence of Teacher Involvement and Compensation on the Performance of Teachers of Batam State Vocational Middle School Teachers has a significant effect both partially and simultaneously at a 100% confidence level. The value of R Square in this study is 0.644 which means that only 64.4% changes in employee performance levels can be explained by Competency, Teacher Involvement, Teacher Performance and Teacher Compensation at Batam Vocational High School while the rest are influenced by other variables that are not observed. in this research. Keywords: Competence, Employee Engagement, Compensation, and Employee Performance